Feasibility study on the use of 3D silicon microdosimeter detectors for microdosimetric analysis in boron neutron capture therapy. (October 2018) - Hu, N.; Uchida, R.; Tran, L.T.; Rosenfeld, A.; Sakurai, Y.
Abstract: This paper presents the feasibility study of a novel 3D mesa bridge microdosimeter and its use for BNCT dosimetry. The performance of the microdosimeter was studied using Monte Carlo simulation. The clinical BNCT field at Kyoto University Reactor (KUR) using both thermal and epithermal irradiation modes were used in this study. Results show that this microdosimeter can be utilised as an effective tool to measure microdosimetric spectrum in the BNCT field and experimental validation will follow once KUR is operational. Highlights: Use of silicon microdosimeters for BNCT dosimetry is proposed. Optimisation of boron converter thickness is necessary. Detector geometry affects the calculated microdosimetric spectrum. A 2 µm thick silicon microdosimeter was found to be the optimum thickness. Measurements will be conducted to verify the results once KUR is operational.